Heterogeneous Solvent Dielectric Relaxation in Polymer Solutions of Water and Alcohols - Sasaki, Kaito; Bandai, Kenta; Takatsuka, Masanobu; Fujii, Mitsuki; Takagi, Minato; Kita, Rio; Yagihara, Shin; Kimura, Hiroshi; Shinyashiki, Naoki (Frontiers in Physics, 2020)
The dynamics of polymer solutions are heterogeneous. The different molecule sizes and structures cause different mobilities of polymers and solvents. Recently, regarding the heterogeneity of water, two dielectric relaxation processes of water were argued in several supercooled polymer–water mixtures. To investigate whether this is unique to water, we performed broadband dielectric spectroscopy measurements of poly(vinylpyrrolidone)–water (PVP–water), PVP–propylene glycol, PVP–ethylene glycol, and PVP–propanol mixtures with 65 wt% PVP in a temperature range of 123–298 K. For the PVP–water mixture, α-relaxation of PVP and two distinct relaxation processes appeared simultaneously: one was the primary relaxation process of water (fast water process) and the other was the relatively small relaxation process (slow process), at a frequency between that of the α-process of PVP and the fast water process. The strength ratio of the large fast water and small slow processes remained nearly constant in all the temperatures measured. For the PVP–alcohol mixtures, in addition to the α-process of PVP, two or three relaxation processes of alcohol appeared. The primary relaxation process of alcohol above 240 K changed to the small fast secondary process. The small slow processes, which can be recognized below 240 K (the glass transition temperature of the α-process of PVP, Tg,PVP) appears at intermediate frequency between that of the PVP α-process and the primary process of alcohol. The small slow process changed to the primary larger process. The properties of the multiple relaxation processes of solvents below Tg,PVP in PVP–alcohol mixtures are completely different from those in PVP–water mixture.